Chronic traumatic encephalopathy in blast-exposed military veterans and a blast neurotrauma mouse model. - Goldstein, L; Fisher, A; Tagge, C; Zhang, X; Velisek, L; Sullivan, J; Upreti, C; Kracht, J; Ericsson, M; Wojnarowicz, M; Goletiani, C; Maglakelidze, G; et al. (2012)
Blast exposure is associated with traumatic brain injury (TBI), neuropsychiatric symptoms, and long-term cognitive disability. We examined a case series of postmortem brains from U.S. military veterans exposed to blast and/or concussive injury. We found evidence of chronic traumatic encephalopathy (CTE), a tau protein-linked neurodegenerative disease, that was similar to the CTE neuropathology observed in young amateur American football players and a professional wrestler with histories of concussive injuries. We developed a blast neurotrauma mouse model that recapitulated CTE-linked neuropathology in wild-type C57BL/6 mice 2 weeks after exposure to a single blast. Blast-exposed mice demonstrated phosphorylated tauopathy, myelinated axonopathy, microvasculopathy, chronic neuroinflammation, and neurodegeneration in the absence of macroscopic tissue damage or hemorrhage. Blast exposure induced persistent hippocampal-dependent learning and memory deficits that persisted for at least 1 month and correlated with impaired axonal conduction and defective activity-dependent long-term potentiation of synaptic transmission. Intracerebral pressure recordings demonstrated that shock waves traversed the mouse brain with minimal change and without thoracic contributions. Kinematic analysis revealed blast-induced head oscillation at accelerations sufficient to cause brain injury. Head immobilization during blast exposure prevented blast-induced learning and memory deficits. The contribution of blast wind to injurious head acceleration may be a primary injury mechanism leading to blast-related TBI and CTE. These results identify common pathogenic determinants leading to CTE in blast-exposed military veterans and head-injured athletes and additionally provide mechanistic evidence linking blast exposure to persistent impairments in neurophysiological function, learning, and memory.